L’hypothèse de l’inconnaissance dans les dynamiques d’(in)visibilisation de la ville informelle - Franck Dorso (Territoire en Mouvement)
The text proposes to explore the dynamics of visibility and invisibility relating to informal practices in urban spaces, by focusing the approach on the modes of production of knowledge of the actors on each other and on their practices. The comparison of three case studies in Turkey, Brazil and France allows to explore different variations on the link between knowledge and power. It leads to the identification of a singular mode based on an absence of knowledge, which seems to be less of a lack than a strategic and tactical choice, and for which the provisional term of unknowledge is proposed. The contribution presents the contours of this dynamic, before considering the implications in terms of operational action, circulation and research.